Braiding Public Health and Human Rights: AIDS, Activism, and International Agencies in Brazil, 1987–1996. Issue 1 (2nd March 2023) - Cueto, Marcos; Lopes, Gabriel
Abstract: This article examines the emergence of a synergy that allowed the early development of what was once considered the best anti-AIDS program in the developing world. Initial responses to AIDS in Brazil during the 1980s and early 1990s were marked by a confrontation between activists concerned with human rights, and a government focusing on biomedical management of the epidemic. After 1992, activists, medical researchers, government officials, international donors like the Ford Foundation, health officers, and multilateral agencies like the World Bank were galvanized to cooperate. This was a complex process of braiding knowledge and practices related to activism, science, public health, governance and philanthropy in which each constituency maintained its independence. The result was a complex, holistic, and nuanced AIDS program. The process helped bridge the gap between knowledge and advocacy, generated public awareness, and was instrumental to reducing AIDS mortality developing local human resources and comprehensive policies.